Emotion, self-concept and relationships in intrafamily sex offenders through the Rorschach psichodiagnostic - Artica, Juan (2014)
This descripted research was performed with the objective of knowing the affective traits, self-concept and interpersonal relationships in intrafamiliar sex offenders. For that purpose, it was applied the Rorschach Psycodiagnostic and a survey that collected demographic data and information on sexual assault committed by the participants. The sample consists of 30 inmates of a correctional facility, identified as having committed sexual crimes against sexual freedom and domestic abuse. According to the results, it is disclosed that the group of intrafamiliar sex-offenders are characterized by scarce resources to control intense emotional shock; responding impulsively in these situations. Also, a self-assessment is impregnated of nuances of negative self-observed, generating such a defensive devaluation of narcissistic strategy to deny the pain and limitation. Similarly, emotional constriction states are shown, that is, there is a poor emotional expression. On the other hand, it is shown a tendency to focus on themselves more than usual, making it difficult to see things from other perspectives, also presents difficulties to establish deep and meaningful relationships.